Practicing Embodied Thinking in Research and Learning (Routledge International Studies in the Philosophy of Education, 2025)
This book delves into the embodied ground of thinking, illuminating the transition from theorising about the embodied mind to actively practising embodied thinking in research, teaching, and learning. The authors speak from immersing themselves in novel methods that engage the felt, experiential dimensions of cognition in inquiry. The turn to embodiment has sparked the development of new methodologies within phenomenology, pragmatism, and cognitive science. Drawing on Eugene Gendlin’s philosophical work on felt understanding, and Francesco Varela’s enactivist approach, contributors explore innovative embodied thinking methods such as Focusing, Thinking at the Edge, micro-phenomenology, and mindfulness practices. They demonstrate the practical applications of these methods in research, teaching, and learning, highlighting their liberating and empowering potential for researchers and students. In an age marked by information overload and societal polarisation, methods of embodied thinking provide an innovative edge to critique, complementing more traditional approaches to critical thinking with listening skills and reflexive care. This book shows how heeding the essential, yet often overlooked, embodied grounds of critical and creative thinking can deepen and strengthen each of research, teaching, and learning. It will interest philosophers of education and educators in higher education in particular, as well as researchers and postgraduate students from philosophy, and the cognitive and social sciences, who are curious about how embodied thinking can enrich research, teaching, and learning.